Protecting Islamic Users In E-Payment Transaction: The Islamic Perspective - Abdul Razak, Nurul Asikin; Ahmad, Shofian; Zakaria, Zamzuri (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
Vulnerability of Islamic users in e-payment transactions, including risks related to fraud, privacy breaches, and ethical violations. These concerns arise due to the rapid digital transformation and the evolving landscape of financial technologies. In today's digital era, electronic payment (e-payment) systems play a pivotal role in facilitating transactions across global economies. However, alongside their convenience, e-payment systems present significant challenges related to security, privacy, and ethical considerations, particularly when viewed through the lens of Islamic finance. The objective of this study is to examine how Islamic principles can guide the development and implementation of e-payment systems to protect users effectively. It aims to identify key principles from Islamic finance that can enhance security, ensure fairness, and uphold ethical standards in e-payment transactions. This study adopts a qualitative research method, focusing on documentation and secondary sources, by examining and analyzing users protection in e-payment transactions from an Islamic perspective. Through an analysis of Islamic financial principles such as transparency, fairness, security, and ethical conduct, this paper finds that integrating these principles into e-payment systems can mitigate risks and enhance user confidence. Moreover, avoiding uncertainty (gharar) and gambling (maysir) in e-payment transactions underscores the importance of clear and non-speculative terms. The implications of this study are significant for stakeholders in the e-payment industry, including financial institutions, regulatory bodies, and policymakers. By aligning e-payment practices with Islamic ethical norms, stakeholders can foster trust among Islamic users, enhance regulatory compliance, and promote sustainable economic development. This paper underscores the importance of integrating Islamic ethical principles into e-payment systems to ensure the protection and welfare of Islamic users.